2019
DOI: 10.1097/sla.0000000000003746
|View full text |Cite
|
Sign up to set email alerts
|

Is Immediate Lymphatic Reconstruction Cost-effective?

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 35 publications
(92 reference statements)
0
52
0
Order By: Relevance
“…Similar costing methods have been used for other plastic surgery procedures, including lymphatic surgery and breast reconstruction. [24][25][26] Societal or patient perspectives could also be considered; however, we have no reason to think these vantages would vary significantly. Patients who suffer mutilating hand injuries often require significant time-off of work, regardless of which reconstruction they undergo.…”
Section: Discussionmentioning
confidence: 99%
“…Similar costing methods have been used for other plastic surgery procedures, including lymphatic surgery and breast reconstruction. [24][25][26] Societal or patient perspectives could also be considered; however, we have no reason to think these vantages would vary significantly. Patients who suffer mutilating hand injuries often require significant time-off of work, regardless of which reconstruction they undergo.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study performed a cost-utility analysis to evaluate and compare the cost and quality of life of patients undergoing ALND and ALND with RLNR, with and without LYMPHA, for patients with node-positive breast cancer 55 The addition of LYMPHA to ALND supposed an incremental cost of $2140.00, which was justified by a net clinical benefit of 1.35 quality-adjusted life years (QALYs) of ALND with LYMPHA (30.22 QALY) over ALND only (28.87 QALY). ALND and LYMPHA were more cost-effective with an incremental cost-utility ratios (ICUR) of $1587.73/QALY.…”
Section: Cost-efficacy Of Prophylactic Lymphovenous Anastomosismentioning
confidence: 99%
“…This article confirmed that the additional costs of primary prevention for LE can be justified from a cost-utility perspective for patients with both ALND and ALND with RLNR, especially considering that the complication rates of adding LYMPHA are negligible. 55…”
Section: Cost-efficacy Of Prophylactic Lymphovenous Anastomosismentioning
confidence: 99%
“…It is estimated that 16%–49% of patients who undergo LND develop this disease. 1 5 Despite compliance with lifelong compression garments and manual lymphatic drainage, patients may still show disease progression.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…17 The cost-effectiveness of ILR (after ALND ± radiation) was examined and found to be the more cost-effect treatment option (compared with ALND ± radiation without ILR) for node-positive breast cancer. 1 …”
Section: Introduction and Literature Reviewmentioning
confidence: 99%